Next-Generation mRNA Therapeutics: Self-Amplifying, Thermostable and Personalized mRNA Vaccines in the Era of Precision Medicine - Kapadiya Kris Prakashchandra (International Journal of Vaccines, 2025)
Messenger RNA (mRNA) technology has brought a major change in modern medicine, especially after its successful use in COVID-19 vaccines. However, early mRNA vaccines faced several problems such as low stability, strict cold storage requirements, and lack of personalized treatment. To overcome these challenges, next-generation mRNA technologies have been developed, including self-amplifying mRNA (saRNA), thermostable mRNA vaccines, and personalized mRNA vaccines. This article discusses the development of mRNA therapeutics, the limitations of first-generation mRNA vaccines, and recent progress in advanced mRNA systems. The structure, working mechanism, benefits, and uses of saRNA are explained. The importance of thermostable mRNA vaccines and the methods used to improve their heat stability are also described along with their benefits for global health. The concept of personalized mRNA vaccines, especially for cancer treatment and precision oncology, is highlighted. In addition, different delivery systems such as lipid nanoparticles, polymer-based carriers, and targeted delivery methods are included. The role of artificial intelligence in mRNA design, applications beyond COVID-19, safety, regulatory aspects, and future possibilities of mRNA therapeutics are also discussed. This article aims to give a clear and updated understanding of next-generation mRNA therapeutics.
Keywords: 1. mRNA therapeutics 2. Self-amplifying mRNA 3. Thermostable mRNA vaccines 4. Personalized cancer vaccines 5. Precision medicine